2022
DOI: 10.17711/sm.0185-3325.2022.017
|View full text |Cite
|
Sign up to set email alerts
|

Association between screen time exposure, anxiety, and sleep quality in adolescents

Abstract: Introduction. The increase in sedentary screen time can negatively affect the quality of sleep, impacting the performance of daily activities. Objective. To analyze the association between sedentary screen time and sleep quality, regardless of the symptoms of anxiety in adolescents of both genders. Method. Cross-sectional study integrating school-based epidemiological research with a representative sample (n = 666) of high school students (14 to 19 years old) in public schools in the municipality of Caruaru-PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The authors suggest that an inadequate practice of sleep hygiene can operate in a population with psychopathology where is more predisposition to insomnia. The results of Santiago et al (2022) partially support this statement. Indeed, Sandoval-Rincón et al ( 2022) found that patients with major depression comorbid with insomnia were the group with the worst practice of sleep hygiene.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…The authors suggest that an inadequate practice of sleep hygiene can operate in a population with psychopathology where is more predisposition to insomnia. The results of Santiago et al (2022) partially support this statement. Indeed, Sandoval-Rincón et al ( 2022) found that patients with major depression comorbid with insomnia were the group with the worst practice of sleep hygiene.…”
supporting
confidence: 53%
“…Its potential effects on sleep have received particular attention. Santiago et al (2022) assessed the association between sedentary screen time and sleep quality in Brazilian adolescents. They found that excessive screen time (≥ 4 hours) in interactive devices (computers and videogames) was significantly associated with poor sleep quality only in adolescents with anxiety risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with previous studies that suggest a positive correlation between excessive screen time and anxiety. [38][39][40] The immersive nature of binge-watching, which may involve emotional investment in the content, could contribute to heightened anxiety levels. 10 BWA was also positively associated with depression, as indicated by a beta coefficient of 0.450.…”
mentioning
confidence: 99%